1
$\begingroup$

enter image description here My turn: Let the equation of the curve is $$y=f(x)$$ Then the slope of the tangent is $$\frac{dy}{dx}$$ The equation of the tangent at some point $x_o$ Is $$y= f'(x_o) x + b $$ , $$b = f(x_o) -x_o f'(x_o)$$ Now the area of the triangle is $$A = 0.5 \frac{x_o f'(x_o) -f(x_o)}{f'(x_o)}\times (f(x_o) -x_o f'(x_o))$$ Now i think i need to put A as a constant an integrate the last equation with respect to $x_o$ to get the equation of th as a e curve but i am confused with how can i consider $x_o$ as a variable even though it is constant ?

$\endgroup$
  • $\begingroup$ It is a difficult problem see my answer below. $\endgroup$ – Dr Zafar Ahmed DSc Oct 25 '19 at 19:37
0
$\begingroup$

I would write $$A=\frac{1}{2}\frac{(y_0-f'(x_0)x_0)^2}{|f'(x_0)|}$$ It is $$A=\frac{1}{2}\frac{(f(x_0)-x0_0f'(x_0))^2}{|f'(x_0)|}$$

$\endgroup$
  • $\begingroup$ Okay, can i integrate this to get the equation of the curve ?Dr.Sonnhard Graubner $\endgroup$ – Hussien Mohamed Oct 25 '19 at 12:40
  • $\begingroup$ I think $x_0-f'(x_0)x_0$ should be $f(x_0)-f'(x_0)x_0$. $\endgroup$ – David K Oct 25 '19 at 12:44
  • $\begingroup$ Yes you have right, just corrected! $\endgroup$ – Dr. Sonnhard Graubner Oct 25 '19 at 12:52
0
$\begingroup$

It is difficult problem

The intercets on $x$ and $y$ axes by the tangent at the point $(x,y)$ are $\Delta x=x-ydx/dy$ and $\Delta y=y-xdy/dx.$ Then the area of the triangle with thes intercepts is $$|\frac{1}{2} (x-ydx/dy)(y-xdy/dx)|=A^2~~~(1)$$ Let us denote $\frac{dy}{dx}=p$ and let $B^2p>0$ Then we have $$x^2p^2+y^2-2xyp=B^2 p \implies |y-xp|= B\sqrt{p}~~~(2)$$ $$y=xp+B\sqrt{p} \implies y=x\frac{dy}{dx}+B\sqrt{\frac{dy}{dx}}~~~(3)$$ D.w.r.t.x to get $$y'=xy''+y'+ \frac{B}{2}\sqrt{\frac{dx}{dy}} y'' \implies y'' \left [x+\frac{B}{2}\sqrt{\frac{dx}{dy}} \right]=0~~~~(4)$$ $y''=0$ gives trivial solution $(y'=C$) which can be put in (3) to get the general solution of the first order ODE (3) which will be family of lines. For a fixed non-trivial solution of (3), we take $$\frac{B}{2}\sqrt{\frac{dx}{dy}}=-x \implies dy= \frac{B^2}{4x^2}dx \implies \int dy=\frac{B^2}{4} \int \frac{dx}{x^2}~~~~(5)$$ Finally, we get $$xy=-\frac{B^2}{4}~~~~(6),$$ the rectangular hyperbola. Note that this (6) is the singular solution of the Clairaut equaion (3). Here $B$ or $A$ is a fixed given constant.

Notte: it is rather simple to show the converse that the itercepts of the tangents to the curve $xy=D^2$ make a triangle of constant area.

$\endgroup$
  • $\begingroup$ That is the same result i got but with different notations , would integrate it to get y ? Dr Zafar Ahmed DSc $\endgroup$ – Hussien Mohamed Oct 25 '19 at 13:36
  • $\begingroup$ @Hussain Mohamed It is a difficult prob\em see my edited answer. $\endgroup$ – Dr Zafar Ahmed DSc Oct 25 '19 at 19:36

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.